OPTIMIZATION OF GENDER EQUALITY IN THE EDUCATION SECTOR TO ACCELERATE THE DEVELOPMENT OF SULAWESI UTARA PROVINCE - Wijayanto, Rafael O. (FEB Universitas Sam Ratulangi Manado, 2024)
Gender issues in education for development acceleration require more targeted data-based handling. Especially if this issue is developed within the framework of optimizing regional social capital. However, there has been no quantitative analysis that comprehensively dissects gender data within the framework of utilizing social capital for accelerating regional development in more depth, especially in the education sector. This study aims to obtain deeper information about the gender equality profile in education for development acceleration in Sulawesi Utara Province. Using secondary data from the 2022 SUSENAS, BPS data collection of 8,536 respondents spread across all regencies/cities in Sulawesi Utara. Descriptive quantitative analysis was carried out on the variables of education, employment and gender. The results of the study stated that there has been progress in reducing the gender gap in education in Sulawesi Utara. However, there are still challenges, especially in rural areas. Greater efforts are needed to improve access, quality, and awareness of education for women in order to achieve better gender equality in education.